Analisis Regulasi Sukuk oleh Otoritas Jasa Keuangan dalam Peningkatan Berinvestasi di Pasar Modal Indonesia - Nasfi, Nasfi; Dewi, Sandra (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
The purpose of writing is to determine the regulations of the Financial Services Authority (OJK) on issuers that invest and an increase in the number of issuers investing in the capital market each period, whether it has increased or decreased. The research method is field research (field research) using a qualitative approach, which is to try to describe and explain and collect detailed information using data collection procedures during the case occurred. The data collection technique used is by interviewing and using secondary data found on the website of the Financial Services Authority (OJK). The results of the study, it can be concluded that the Regulation from the Financial Services Authority (OJK) is to ensure the safety of investors in investing, and the number of issuers investing is still experiencing a decline, this is because the role of the Financial Services Authority (OJK) office does not only focus on supervision and regulation of the service industry. finance but also carry out the function of education and protection of financial consumers, such as the rampant illegal investment offers that are quite unsettling to the public.